When is "Too Much" Inequality Not Enough? The Selection of Israeli Emigrants - Eric Gould; Omer Moav (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
This paper examines the effect of inequality on the incentives to emigrate according to a person's education and unobservable skills (residual wage). Borjas (1987) shows that higher skilled individuals are more likely to emigrate than lower skilled individuals when the returns to skill are higher in a potential foreign destination. Using a unique data set on Israeli emigrants, we show that the probability of emigrating indeed increases monotonically with education. However, the relationship between residual wages and emigration rates exhibits an inverse u-shaped pattern. We build a model to explain both of these patterns by incorporating the idea that education is a "general" skill which can be transferred to a foreign country, but residual wages are composed of "general" and "country-specific skills" which are not easily transferable. We test the model's predictions by exploiting variation in the patterns of emigration across industries and occupations. Our findings are consistent with the theory, and therefore, highlight the importance of differentiating between general and "country-specific" skills in order to understand emigrant selection.
Keywords: 330